Intellectual Work and the Spirit of Capitalism - Kemple, Thomas. author. aut Link
XIV, 266 p.
Keywords: This book offers a unique and accessible way of conceptualizing the vocations of art, science, and politics in the capitalist world through an examination of some neglected features of the work of the scholar who first traced their origins and consequences in 'the West': Max Weber.